2020
DOI: 10.1111/head.14007
|View full text |Cite
|
Sign up to set email alerts
|

Eptinezumab Demonstrated Efficacy in Sustained Prevention of Episodic and Chronic Migraine Beginning on Day 1 After Dosing

Abstract: Objective.-To determine the onset of preventive efficacy with eptinezumab in patients with migraine. Background.-Eptinezumab is a monoclonal antibody inhibiting calcitonin gene-related peptide approved as an intravenously administered treatment for the prevention of migraine. Methods.-Patients who received eptinezumab 100 mg, eptinezumab 300 mg, or placebo in PROMISE-1 (episodic migraine; 100 mg, n = 221; 300 mg, n = 222; placebo, n = 222) or PROMISE-2 (chronic migraine; 100 mg, n = 356; 300 mg, n = 350; place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 34 publications
3
40
1
Order By: Relevance
“…Similarly, with fremanezumab, significant reductions compared with placebo in migraine days were observed as early as the second study day (first full day following injection) (27). With eptinezumab, the percentage of participants with a migraine was reduced on day 1 after the first dose compared with placebo (28). The benefit of treatment with erenumab vs placebo reached significance on day 3 after the higher dose (140 mg) was administered, and on day 7 after the lower dose (70 mg) (29).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, with fremanezumab, significant reductions compared with placebo in migraine days were observed as early as the second study day (first full day following injection) (27). With eptinezumab, the percentage of participants with a migraine was reduced on day 1 after the first dose compared with placebo (28). The benefit of treatment with erenumab vs placebo reached significance on day 3 after the higher dose (140 mg) was administered, and on day 7 after the lower dose (70 mg) (29).…”
Section: Discussionmentioning
confidence: 95%
“…CI confidence interval, HIT-6 6-item Headache Impact Test, LS least squares, mTOQ-6 The estimated mean, mean difference from placebo, and 95% CI are from an analysis of covariance adjusted for baseline value and stratification factors of concomitant treatment and region c Worse includes "minimally worse", "much worse", and "very much worse" headache frequency on a longer term basis. should be noted that, as a preventive treatment, eptinezumab is administered every 12 weeks, with a previous analysis showing statistically significant preventive efficacy relative to placebo beginning on post-treatment day 1 and extending through the 12-week dosing interval [26]; therefore, some of the effect on week 4 outcomes was likely related to the rapid onset of preventive efficacy with eptinezumab. These findings confirm the substantial burden that migraine places on patients and identified a treatment benefit in favor of eptinezumab compared with placebo in relieving the disease burden in patients experiencing up to 15 migraine days per month.…”
Section: Discussionmentioning
confidence: 98%
“…These trials evaluated a range of eptinezumab doses, including 10 mg, 30 mg, 100 mg, 300 mg, and 1000 mg, and included a phase 1b trial in patients with episodic migraine (EM), a phase 2 trial in patients with chronic migraine (CM), and the two pivotal phase 3 trials, PROMISE-1 in patients with EM and PROMISE-2 in patients with CM. PROMISE-1 and PROMISE-2 found that eptinezumab 100 mg and 300 mg met the primary efficacy endpoint of significantly reducing mean monthly migraine headache days over weeks 1–12 [ 24 , 25 ], with preventive benefits observed in the 24 h after dosing [ 26 ]. Based on these findings, the approved doses in the United States are eptinezumab 100 mg and 300 mg administered intravenously for the prevention of migraine.…”
Section: Introductionmentioning
confidence: 99%